Theoretical and Experimental Investigations of Spectroscopic Properties of 2-Thiophenecarbonyl chloride. Issue 2 (December 2018) - Han, Ligang; Tao, Yaping; Liu, Zhaojun
Abstract: Molecular structure and vibrational wave numbers for 2-Thiophenecarbonyl chloride have been computed using the B3LYP method with the 6-311++G (d, p) basis set. The computation reveals that the title compound has two minimal conformers (gauche and syn). The conformational energy difference between the syn and gauche is very small, indicating that the syn conformer coexists with the gauche conformer. FT-IR and FT-Raman spectra of 2-Thiophenecarbonyl chloride were recorded and analysed in the range 3500-400 and 3500-200cm-1, respectively. The HOMO-LUMO energy gap of the two conformers have been also calculated for comparison of their chemical activities.